Exploring the Extent of Phosphorus and Heavy Metal Uptake by Single Cells of Saccharomyces cerevisiae and Their Effects on Intrinsic Elements by SC-ICP-TOF-MS - Qin, Wen; Stärk, Hans-Joachim; Müller, Susann; Reemtsma, Thorsten (Frontiers in Microbiology, 2022)
The effect of six heavy metals, Ag, Pb, Pd, Cu, Ni and Cr, on P uptake by yeast was investigated by single-cell analysis using inductively coupled plasma time-of-flight mass spectrometry (SC-ICP-TOF-MS). It was found that the P content in cells with 1.55 g L-1 P feeding after P starvation was increased by ~ 70 % compared to control cells. Heavy metals at 10 ppm, except Cu, had a negative impact on P accumulation by cells. Pd reduced the P content by 26 % in single cells compared to control cells. Metal uptake was strongest for Ag and Pd (0.7 × 10-12 L cell-1) and weakest for Cr (0.05 × 10-12 L cell-1). Exposure to Cr markedly reduced (- 50 %) Mg in cells and had the greatest impact on the intrinsic element composition. The SC-ICP-TOF-MS shows the diversity of elemental content in single cells: for example, the P content under standard conditions varied between 12.4 to 890 fg cell-1. This technique allows to study both, the uptake of elements and sublethal effects on the physiology at a single cell level.